The Links between the Price of Oil and the Value of US Dollar - Zhang, Yi (International Journal of Energy Economics and Policy, 2013)
Using monthly data, this paper studies the cointegration between the real price of oil and the real effective exchange rate of US dollar allowing for structural breaks. Contrary to the conclusion from previous literature, this paper finds that the cointegration between the oil price and the value of US dollar does not significantly exist unless the effects of two structural breaks in the past, November 1986 and February 2005, are controlled for. Keywords: Oil price; Exchange rate; Cointegration JEL Classifications: C32; F31; Q43